THE LEGAL CERTAINTY OF ELECTRONIC EVIDENCE AUTHENTICATION UNDER THE CIVIL PROCEDURE LAW IN INDONESIA - Kevien Dicky Aldison; Patricia Audrey Ruslijanto; M. Sudirman (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study examines the legal certainty of electronic evidence authentication under the Civil Procedure Law in Indonesia. The research highlights the importance of providing regulation to authenticate electronic evidence, as stated in Article 5 of Law Number 1 of 2024, which concerns the Second Amendment to Law Number 11 of 2008 regarding Electronic Information and Transactions. The study adopts a normative juridical approach; the researcher's focus in this legal research is on legal principles and legal inventory research. The researcher aims to analyze the legal principles governing electronic evidence and its authentication process in civil procedure law. The primary purpose of this research is to ensure that legal certainty regarding the authentication of electronic evidence is achieved perfectly and comprehensively. It is considered necessary, given that civil procedure law in Indonesia has not explicitly regulated the authentication mechanism for electronic evidence until now. Therefore, by adding legal provisions that specifically restrict the authentication of electronic evidence in civil procedure law, the value of legal certainty can be achieved fully and comprehensively. This research is expected to contribute in the form of conceptual and normative analysis that can strengthen the argument regarding the urgency of regulating the authentication of electronic evidence. Thus, the results of this research not only provide an academic foundation but also offer constructive ideas that are relevant to the development of civil procedure law in Indonesia, particularly in the context of resolving civil disputes involving the use of electronic evidence.